Endoscopic Obturation of Esophageal and Gastric Varices with a Cyanoacrylic Tissue Adhesive - Jean-Pierre Gotlib (Canadian Journal of Gastroenterology)
An original method of obturation of esophageal and gastric varices with a cyanoacrylic glue has been used for nine years. This method allows treatment of gastric and very large esophageal varices, which is difficult with common endoscopic sclerotherapy, and makes hemostasis in case of acute bleeding easier. There are few complications, none lethal.